David Busch's Canon EOS R8 Guide to Digital Photography - Busch, David D. (David Busch Camera Guide Series., 2024)
David Busch's Canon EOS R8 Guide to Digital Photography is your all-in-one comprehensive resource and reference for the exciting new Canon EOS R8, which is aimed squarely at enthusiasts looking for an affordable full-frame entry to mirrorless photography. It boasts a 24.2 sensor with superior low-light performance and action-friendly 40 frames-per second continuous shooting capabilities. Advanced video features include 4K and HDR video, and 10-bit C-log3 capture for sophisticated color grading. Three available adapters make it easy to supplement your RF-mount lenses with a broad selection of legacy Canon EF and EF-S optics. The R8 also features wireless connectivity to computers and smart devices. With this book in hand, you can quickly apply all these advanced features to your digital photography, while boosting your creativity to take great photographs with your Canon EOS R8. Filled with detailed how-to steps and full-color illustrations, David Busch's Canon EOS R8 Guide to Digital Photography covers all this upscale camera's features in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included is the handy "roadmap" chapter, an easy-to-use visual guide to the cameras' features and controls. Learn when to use each option and, more importantly, when not to use them, by following the author's recommended settings for every menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera's capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Canon EOS R8.